2008
DOI: 10.3354/meps07243
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and growth response to temperature and salinity of psychrophilic, halotolerant Chlamydomonas sp. ARC isolated from Chukchi Sea ice

Abstract: Sea ice provides a habitat for a diverse community of microorganisms, which comprise a substantial portion of primary production in ice-covered seas. Organisms immured in sea ice have to withstand strong changes in temperature and salinity. We report on the growth rate response to salinity and temperature of the chlorophyte Chlamydomonas sp. ARC, isolated from land-fast sea ice in the Chukchi Sea, Alaska. We found it to be a euryhaline psychrophile capable of growth at temperatures as low as -5°C and at salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…As shown in Fig. 1, we also confirmed that the psychrophilic strains isolated by Eddie et al (2008), Liu et al (2006) and Leya (2004) form a monophyletic lineage within Microglena, called the Polar-subclade.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…As shown in Fig. 1, we also confirmed that the psychrophilic strains isolated by Eddie et al (2008), Liu et al (2006) and Leya (2004) form a monophyletic lineage within Microglena, called the Polar-subclade.…”
Section: Discussionsupporting
confidence: 70%
“…Among Microglena species the pyrenoid is very variable in shape, but all strains have in common that the pyrenoid is surrounded by several or many starch grains arranged in parallel rows. This was also reported by Ettl & Green (1973) for M. reginae, by Rosowski & Hoshaw (1988) for M. longirubra, and Eddie et al (2008) and Liu et al (2006) for two unidentified psychrophilic Chlamydomonas strains, based on electron microscopical investigations. Pyrenoid shape varies according to morphotype (Fig.…”
Section: Chloroplast Morphology and Phenotypic Plasticity In Microglenamentioning
confidence: 67%
See 3 more Smart Citations